Positioning Malaysia as halal-hub: Integration role of supply chain strategy and halal assurance system - Nik Muhammad, Nik Maheran; Md Isa, Filzah; Kifli, Bidin Chee (Canadian Center of Science and Education, 2009)
HALAL-HUB is a concerted effort among the Islamic organizations/bodies such as Halal manufacturers, Halal traders, buyers, and consumers from all over the world.To be the central trading hub for Halal products, Malaysia must intelligently market itself and achieved Halal-hub main objective of providing a credible platform in connecting global Halal supply-chain and certification for Halal Assurance.Existing literature provides a number of examples that illustrate how supply chain strategy and marketing intelligence improve firm’s performance.The literature, however, lacks theoretical support to facilitate an understanding of the magnitude of supply change strategies, structure of halal assurance system and marketing intelligence to support the scope of relational of Halal-hub.This article uses the strategy structure-performance paradigm to position Halal Hub relative to the nature of relationships within the broader supply chain strategies, Halal Assurance systems and marketing intelligence a firm employs.The framework presented is a first step towards a more holistic and theory-based approach to understanding the link between, supply chain, halal assurance system, marketing intelligence and Halal-hub.This framework also is designed to serve as a basis for future research in this area.